Complete Whole Genome Sequence of Vibrio parahaemolyticus RP0132 Strain Isolated from Shrimp in Malaysia - Ke-Yan Loo; Loh Teng-Hern Tan; Jodi Woan-Fei Law; Kah-Ooi Chua; Priyia Pusparajah; Learn-Han Lee; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
Vibrio parahaemolyticus is a Gram-negative, halophilic bacterium that is ubiquitous in marine environments. Its perilous co-existence with aquatic animals increases the risk of infections and diseases, especially those in aquaculture systems, thus resulting in reduced production and economic losses in the aquaculture industry. Moreover, V. parahaemolyticus can be easily transmitted to humans via consumption of contaminated seafood, resulting in gastroenteritis outbreaks. However, the rise in multidrug resistance within the species has challenged the efficacy of antimicrobial treatments against V. parahaemolyticus infections. Therefore, we report the genome sequence of V. parahaemolyticus RP0132 isolated from shrimp to gain insight into its antimicrobial resistance traits and potential resistance mechanisms. The findings will facilitate the development of effective anti-Vibrio agents to manage V. parahaemolyticus infections.